2006
DOI: 10.1099/mic.0.28500-0
|View full text |Cite
|
Sign up to set email alerts
|

Production and properties of the native Chromobacterium violaceum fucose-binding lectin (CV-IIL) compared to homologous lectins of Pseudomonas aeruginosa (PA-IIL) and Ralstonia solanacearum (RS-IIL)

Abstract: Chromobacterium violaceum is a versatile, violet pigment (violacein)-producing b-proteobacterium, confined to tropical and subtropical regions, dwelling in soil and water, like Pseudomonas aeruginosa and Ralstonia solanacearum. These three bacteria are saprophytes that occasionally become aggressive opportunistic pathogens virulently attacking animals (the first two) and plants (the third). The recent availability of their genome sequences enabled identification in the C. violaceum genome of an ORF (locus no. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…P. aeruginosa produces a galactophilic lectin PA-IL (LecA) and a fucophilic (+ mannophilic and arabinophilic) lectin PA-IIL (LecB) [3]. C. violaceum also possesses a fucophilic lectin CV-IIL homologous to PA-IIL in structure and major specificity [4]. These three lectins bind to most human cells due to their affinities to their most common antigens [5,6]: PA-IL preferentially binds to the terminal Galα-bearing human blood group epitopes found in P-system, I, and B antigens [5].…”
Section: Introductionmentioning
confidence: 99%
“…P. aeruginosa produces a galactophilic lectin PA-IL (LecA) and a fucophilic (+ mannophilic and arabinophilic) lectin PA-IIL (LecB) [3]. C. violaceum also possesses a fucophilic lectin CV-IIL homologous to PA-IIL in structure and major specificity [4]. These three lectins bind to most human cells due to their affinities to their most common antigens [5,6]: PA-IL preferentially binds to the terminal Galα-bearing human blood group epitopes found in P-system, I, and B antigens [5].…”
Section: Introductionmentioning
confidence: 99%
“…CV-IIL was isolated from C. violaceum (Bergonzini) ATCC 12472, and RSL and RS-IIL -from R. solanacearum ATCC 11696 (purchased from the American Type Culture Collection, ATCC, Manassas, VA), as earlier described (GilboaGarber, 1982;Sudakevitz et al, 2002;Sudakevitz et al, 2004;Zinger-Yosovich et al, 2006). Con A and UEA-I were purchased from Sigma-Aldrich (St. Louis, MO).…”
Section: The Lectin Preparationsmentioning
confidence: 99%
“…They reported that blood-group H-type 1 precursor was expressed in all species investigated [camel, cow, goat, horse (mare), human, pig, rabbit and sheep (ewe)], while only pig, dromedary camel, and rabbit milk proteins carried the H-type 2 epitope, which is important for the inhibition of the adhesion of Helicobacter pylori, Escherichia coli heat-stable toxin, and Campylobacter jejuni to human cells. We have recently used three bacterial lectins (PA-IL, PA-IIL and CV-IIL) of the animal pathogens P. aeruginosa (Gilboa-Garber, 1982) and Chromobacterium violaceum (C. violaceum) (Zinger-Yosovich, Sudakevitz, Imberty, Garber, & Gilboa-Garber, 2006) for the study of diverse mammal milks (Zinger-Yosovich, Iluz, Sudakevitz, & Gilboa-Garber, 2010), showing their different lectin-blocking capacities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fucose-binding lectins are widespread among microorganisms, animals and plants, including Pseudomonas aeruginosa lectin (PA-IIL), Anguilla anguilla agglutinin (AAA), Morone saxatilis agglutinin (MsaFBP32), Dicentrarchus labrax agglutinin, Chromobacterium violaceum lectin (CV-IIL), Ralstonia solanacearum lectin (RS-IIL), Ulex europaeus agglutinin (UEA-I) and Lotus tetragonolobus agglutinin (LTA) (Bianchet et al, 2002;Mitchell et al, 2005;Vandonselaar & Delbaere, 1994;Konami et al, 1990;Zinger-Yosovich et al, 2006;Odom & Vasta, 2006;Cammarata et al, 2001).…”
Section: Introductionmentioning
confidence: 99%